PENGARUH INTERAKSI BELAJAR MENGAJAR DAN MOTIVASI DARI GURU TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AGAMA DI SMK PLUS UMAR ZAHID SEMELO BANDARKEDUNGMULYO JOMBANG TAHUN PELAJARAN 2015/2016 - Nirwan Aflah; Atim S; Muhtadi (FAI- Undar, 2018)
This study aims to find ( 1 ) the influence interaction teaching and learning to student learning achievements on religious subjects in smk plus umar zahid semelo bandarkedungmulyo jombang; ( 2 ) the influence motivation from teachers to student learning achievements on religious subjects in smk plus umar zahid semelo bandarkedungmulyo jombang ( 3 ) the influence interaction teaching and learning and motivation from teachers to student learning achievements on religious subjects in smk plus umar zahid semelo bandarkedungmulyo jombang.This research used a quantitative approach with the kind of research correlational. Population in research are 244 students of smk plus umar zahid semelo bandarkedungmulyo jombang .Technique data collection for measuring variable interaction teaching and learning , the motive for the teacher use chief and techniques data collection for measuring variable learning achievements for religion studies use documentation value raport of a final exam of the semester , while analysis data using spss 19 from the analysis multiple linear regression with the economic situation of significance 0.05 or 0.01.From the analysis of the data obtained some findings , among others, ( 1 ) Teaching and Learning Interactions have a significant effect on learning achievement amounted 0.025 0.025 < 0.05 . ( 2 ) Motivation From Teachers have a very significant influence on learning achievement of 0.002 which is 0.002 < 0.01 . ( 3 ) Interaction Learning and Motivation of teachers simultaneously have a very significant influence amounted 0,000 of which 0,000 < 0.01 . This means that teaching and learning interactions have a significant effect on student student learning achievement, while the motivation of teachers have a very significant influence on student learning achievement , and for Interaction Learning and Motivation of Teachers simultaneously have a very significant influence on Student Learning Achievement in SMK Plus Umar Zahid Semelo Bandarkedungmulyo Jombang.